A Comparison of Functional Outcome of Intra Articular Distal Tib-ial Pilon Fracture Treated by One Stage vs Two Stage Surgically - Punit Talwar; Rahul Kothari; Hemin Singh (National Journal of Medical Research, 2022)
Introduction: The study was conducted to evaluate clinical and functional outcomes of comminuted pilon of distal tibial fractures after surgical management and fixation by modalities available ranging from temporary external fixation, simple distal tibial plates to moderate plating system and intra medullary nails for fibula.